Psycholinguistic Representation of Dyslexia and Intervention Strategies in the Documentary Film Left Behind (2025) - Saiyidinal Firdaus (Austronesian: Journal of Language Science & Literature, 2026)
This study examines the representation of dyslexia and its intervention strategies in the documentary film Left Behind (2025) through a multimodal psycholinguistic framework. While previous research on dyslexia has predominantly focused on clinical and educational contexts, limited attention has been given to how dyslexia is constructed and communicated in audiovisual media. Addressing this gap, the study aims to analyze how cognitive, linguistic, and social dimensions of dyslexia are represented through verbal, audio, and visual modes. This research adopts a qualitative descriptive approach with a systematically operationalized analytical framework that integrates phonological processing, visual–linguistic integration, and sociocultural interaction. Data were collected from selected scenes in the documentary, including dialogue, narration, on-screen text, and cinematic representations of reading practices. The analysis employs explicit coding procedures based on psycholinguistic indicators and multimodal categories, supported by verbatim excerpts and detailed visual descriptions to ensure analytical transparency. The findings reveal that the film represents dyslexia as a multidimensional phenomenon. At the micro-linguistic level, dyslexia is constructed through phonological processing difficulties, such as hesitation, sound repetition, and disrupted decoding. At the cognitive level, visual–linguistic integration challenges are depicted through unstable text tracking and perceptual disorientation. At the sociocultural level, dyslexia is framed as a socially mediated experience shaped by scaffolding, interaction, and affective support. The film also portrays intervention strategies through multisensory learning, assistive technologies, and inclusive pedagogical practices, reflecting the principles of the Active View of Reading. This study contributes to applied linguistics by demonstrating how psycholinguistic constructs can be operationalized within multimodal media analysis, thereby bridging cognitive theory and audiovisual representation.